Interventional management of head and face pain : nerve blocks and beyond - N. Narouze, Samer (Springer New York, 2014)
From the Foreword, by Stewart J. Tepper, MD:   "Dr. Samer Narouze was the first Pain Management anesthesiologist specialist in the US to become Board-certified in Headache Medicine by the United Council of Neurologic Subspecialists (UCNS). It is therefore fitting that he decided to put together a textbook on blocks, interventions, injections, and neuromodulation possibilities in this integrated interdisciplinary area of treatment for head and facial pain...   "This constellation of authors and topics should offer a comprehensive roadmap for interventions to contemplate beyond conventional medications in both primary and secondary head and face pain disorders. The chapters are precise, concise, and immensely readable, and I am honored to have been offered the chance to introduce them and encourage my colleagues to read them."      This is the first book on interventional management of intractable, medically resistant head and face pain.  It is edited and written by world-class leaders in headache medicine and features practical presentations of the entire spectrum of procedures, from simple to complex.  Designed to help shorten the learning curve of practitioners who are beginning to use interventional headache procedures, it provides guidance in identifying patients who are appropriate candidates for this approach and includes a unique compilation of outcomes-based algorithms for different headache and face pain syndromes.   Neurologists, anesthesiologists, pain physicians, physiatrists, neurosurgeons, and interventional radiologists are the intended audience.